Numerical Analysis : an Introduction - Heister, Timo; Rebholz, Leo G.; Xue, Fei, 1977- (De Gruyter, 2019)
Numerical analysis deals with the development and analysis of algorithms for scientific computing, and is in itself a very important part of mathematics, which has become more and more prevalent across the mathematical spectrum. This book is an introduction to numerical methods for solving linear and nonlinear systems of equations as well as ordinary and partial differential equations, and for approximating curves, functions, and integrals.- Resumé vydavatel
Includes index.
Keywords: numerická analýza; numerical analysis; elektronické knihy; učebnice; electronic books; textbooks